Case Report: Neonatal Cholestasis as Early Manifestation of Primary Adrenal Insufficiency - Di Dato, Fabiola; Capalbo, Donatella; Mirra, Rita; Del Vecchio Blanco, Francesca; Salerno, Mariacarolina; Iorio, Raffaele (Frontiers in Pediatrics, 2021)
Neonatal cholestasis (NC) may be due to multiple surgical and nonsurgical causes, some of which are potentially fatal. The list of potential causes of NC is long and the systematic search for each of them is challenging in infants, especially when overt signs of underlying disease are lacking. Endocrinological diseases as causes of NC are rare and sometimes misdiagnosed. We report the case of an infant with prolonged cholestatic jaundice due to adrenal insufficiency suspected because of a single episode of hypoglycemia occurring at birth in the absence of clinical signs of adrenal impairment. Genetic analysis identified a new mutation in MC2R gene in homozygosity as putative responsible for familial glucocorticoid deficiency (FGD). Adrenal insufficiency should always be considered in all cholestatic infants, even in the absence of specific symptoms, since early recognition and treatment is essential to prevent life-threatening events.